2011
DOI: 10.1016/j.vetmic.2011.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Active use of coyotes (Canis latrans) to detect Bovine Tuberculosis in northeastern Michigan, USA

Abstract: Bovine tuberculosis (bTB) is endemic in white-tailed deer (Odocoileus virginianus) in northeastern Michigan, USA, and research suggests transmission to cattle. Prevalence of the disease in deer is estimated at 1.8%, but as prevalence decreases the difficulty of detection increases. Research suggests coyotes (Canis latrans) have a higher prevalence of bTB in Michigan than deer and sampling coyotes may be a more efficient surveillance tool to detect presence or spread of the disease. Coyotes possess suitable eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…These infections in other wildlife were presumably acquired while scavenging on infected deer carcasses (Berentsen et al, 2011), and thus are likely secondary infections, rather than indicators of primary bTB sources. Indeed, 63 of the 82 reports were of strain A, with 42 from coyotes, 14 from opossums, and 7 from raccoons.…”
Section: Wild Cervid Strains Similar To Cattle Strainsmentioning
confidence: 99%
“…These infections in other wildlife were presumably acquired while scavenging on infected deer carcasses (Berentsen et al, 2011), and thus are likely secondary infections, rather than indicators of primary bTB sources. Indeed, 63 of the 82 reports were of strain A, with 42 from coyotes, 14 from opossums, and 7 from raccoons.…”
Section: Wild Cervid Strains Similar To Cattle Strainsmentioning
confidence: 99%
“…Other studies also show that certain carnivorous species, including coyotes, may be used to detect tuberculosis (Berentsen et al 2011). VerCauteren et al (2008 found that obtaining samples from coyotes rather than deer increases the likelihood of detecting Mycobacterium bovis by 40% in TBendemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the use of wildlife sentinel species to monitor environmental disease trends has been reported elsewhere for a variety of zoonotic diseases [5658] and for diseases of agricultural importance, including for monitoring bovine TB [15, 16]. However, such studies have focussed mainly on using wildlife sentinels to monitor patterns of geographic spread of infection within an environment and into previously unaffected areas.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs develop readily identifiable tuberculous lesions in primary predilection sites draining the oropharyngeal cavity, especially the submaxillary lymph nodes [12], but despite high levels of infection they seldom pass on M. bovis infection to conspecifics under New Zealand conditions [13], even though that does occur in some parts of Mediterranean Europe [14]. Carrion-feeders/scavengers have been used as sentinels for TB in other wildlife maintenance hosts, for example, coyotes ( Canis latrans ) in North America being used to indicate persistent M. bovis infection in white-tailed deer ( Odocoileus virginianus [15, 16]). A recent report has suggested that Virginia opossums ( Didelphis virginiana ) may also provide surveillance potential for persistent TB in North America [17].…”
Section: Introductionmentioning
confidence: 99%